Pengaruh Pemberian Penyuluhan terhadap Peningkatan Pengetahuan Mengenai Yoga untuk Mengurangi Nyeri Haid pada Siswi SMA Islam Al-Falah Kota Jambi - Sri Maharani; Fatihatul Hayati; Lulu Fahkrunisa (Jurnal Akademika Baiturrahim Jambi, 2023)
Adolescence is a transitional process from childhood to adulthood which is marked by rapid changes in body development. Adolescence is also known as a period of change, which includes changes in attitudes and physical changes. Dysmenorrhea means pain during menstruation. This condition can get worse when accompanied by unstable psychological conditions, such as stress, depression, excessive anxiety, and excessive sadness or joy. Menstrual pain interferes with women's activities, causing women to try to find ways to reduce the pain they experience. How to reduce menstrual pain can be done in two ways, namely pharmacological and non-pharmacological. Pharmacological ways by taking drugs and non-pharmacological methods can be done with warm compresses or warm baths, massage, physical exercise (exercise), adequate sleep, distractions such as listening to music and relaxation such as yoga. About yoga to reduce menstrual pain. Quantitative research design. The subjects in this study were students in grades I and II of SMA Islam Al-Falah, Jambi City. Research subjects were given a questionnaire about yoga to reduce menstruation during pre and post-counseling about yoga. The research was conducted at Al-Falah Islamic High School, Jambi City. The data collected were analyzed univariately. The purpose of this study is to be used as a source of information for students about the benefits of yoga, especially to reduce menstrual pain. The results of this study are adolescent knowledge about yoga to reduce menstrual pain increases before and after counselling.